Efficacy of Curcumin as Adjuvant Therapy to Induce or Maintain Remission in Ulcerative Colitis Patients: an Evidence-based Clinical Review - Marcellus Simadibrata; Christopher Christian Halimkesuma; Benedicta Mutiara Suwita (Interna Publishing, 2018)
Background: treatment guidelines for ulcerative colitis (UC) not yet established. Currently, mesalazine, corticosteroids, and immunomodulators are treatment options for UC. However, they are known to have unpleaseant side effects such as nausea, vomiting, headaches, hepatitis, and male infertility. Curcumin is found in Turmeric plants (Curcuma longa L.), which possesses both anti-inflammatory and antioxidant properties. This study aimed to determine whether curcumin as adjuvant therapy can induce or maintain remission in UC patients. Methods: structured search in three database (Cochrane, PubMed, Proquest) using "Curcumin", "remission" and "Ulcerative Colitis" as keywords. Inclusion criteria is randomized controlled trials (RCTs), meta-analysis, or systematic review using curcumin as adjuvant therapy in adult UC patients. Results: we found 49 articles. After exclusion, three RCTs were reviewed; two examined curcumin efficacy to induce remission and one for remision maintenance in UC. Curcumin was significantly more effective than placebo in all RCTs. The efficacy of curcumin could be explained by its anti-inflammatory properties, which inhibit NF-kB pathway. Regulation of oxidant/anti-oxidant balance can modify the release of cytokines. However, methods varied between RCTs. Therefore, they cannot be compared objectively. Futhermore, the sample size were small (n= 50, 45, 89) therefore the statistical power was not enough to generate representative results in all UC patients. Conclusion: Available evidence showed that curcumin has the potential to induce and maintain remission in UC patients with no serious side effects. However, further studies with larger sample size are needed to recommend it as adjuvant therapy of ulcerative colitis.